Detection and estimation of nutrient shock effects in bacteria - Azevedo, N. F. (2006)
In this work we have synthesized TiO2 nanoparticles, using either a sol–gel base catalysed process in the interior of CTAB reversed micelles (TiO2 CTAB sol), or the neutralization of a TiO2/H2SO4 solution in the interior of AOT reversed micelles. From the absorption and emission data of the TiO2 nanoparticles it is possible to conclude that in the sol–gel route there remains alkoxide groups in the structure, originating transitions lower than the energy gap of TiO2 semiconductor. These transitions disappear in the neutralization procedure, where the alkoxide groups are absent in the structure.We have assigned the observed indirect and direct optical transitions according to the anatase band structure. TiO2 Langmuir-Blodgett (LB) films were prepared either by direct deposition of titanium isopropoxide or by deposition of the TiO2 CTAB sol. These films showed photoluminescence, which was attributed to band-gap emission and to surface recombination of defect states.